A study of serum magnesium level in hypothyroid cases in a tertiary care hospital, Perambalur - I., Vijayapriya; S., Saravanan (International Journal of Medical Research and Review, 2019)
Magnesium is an incredibly vital mineral found in the human body. Magnesium clearly affects the entire body and naturally will interact with thyroid functions, both directly and indirectly. Objectives: To assess the levels of serum magnesium in patients with hypothyroidism and its correlation with TSH levels. Methodology: An observational study consists of 174 cases of hypothyroidism were selected. All patients with hypothyroidism, newly diagnosed with age above 18years were included, all patients with malignancy, multiple endocrine disorder, CKD and patients supplemented with minerals were excluded in the study. Thyroid function and serum magnesium levels were done and analyzed in these patients. Results: In our study mean serum magnesium level in hypothyroid cases was 2.18±0.02 mg/dl. Our study done with a follow up of thyroid function and serum magnesium level in hypothyroidism after supplementation with thyroid hormone and diet supplementation for magnesium showed a significant improvement which reciprocate the incidence of hypo magnesium in hypothyroidism and which is inversely proportionate to TSH levels which was not statistically significant. Conclusion: The alteration of serum magnesium level in hypothyroidism was not established in our study statistically.